2018
DOI: 10.1074/jbc.m117.816785
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2 and nuclear factor erythroid 2–related factor 2 transcriptionally coactivate xanthine oxidoreductase expression in stressed glioma cells

Abstract: A dynamic network of metabolic adaptations, inflammatory responses and redox homeostasis is known to drive tumor progression. A considerable overlap between these processes exists, but several of their key regulators remain unknown. To this end, here we investigated the role of the proinflammatory cytokine IL-1β in connecting these processes in glioma cells. We found that glucose starvation sensitizes glioma cells to IL-1β-induced apoptosis in a manner that depended on reactive oxygen species (ROS).Although IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…UA administration increased the expression of XO which decreased in response to esculetin treatment ( Figure 5 E). It has been reported that Nrf2 transcriptionally activates XO in glioma cells, which is dependent on Nrf2 and HK2 trafficking to the nucleus [ 17 ]. Esculetin treatment abolished the translocation of HK2 to the nucleus whilst the nuclear import of Nrf2 was upregulated in UA-treated HepG2 cells ( Figure 5 F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UA administration increased the expression of XO which decreased in response to esculetin treatment ( Figure 5 E). It has been reported that Nrf2 transcriptionally activates XO in glioma cells, which is dependent on Nrf2 and HK2 trafficking to the nucleus [ 17 ]. Esculetin treatment abolished the translocation of HK2 to the nucleus whilst the nuclear import of Nrf2 was upregulated in UA-treated HepG2 cells ( Figure 5 F).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that HK2 acts as a transcriptional coactivator of Nrf2 to regulate XO expression. Decreased nuclear translocation in response to HK2 may therefore inhibit XO expression [ 17 ]. We therefore hypothesize that the molecular mechanisms by which esculetin suppresses XO is related to its ability to inhibit the nuclear translocation of HK2 ( Figure 5 F).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that various metabolic enzymes in the cytoplasm and mitochondria could translocate into the nucleus to modify histones and DNA, regulating gene expression (42). A report stated HK2 could translocate into the nucleus as a coactivator participating in redox homeostasis (43). In our ndings, HK2 affected the expression and distribution of phosphorylation of STAT1.…”
Section: Discussionmentioning
confidence: 50%
“…Hexokinase (HK) is recognized as the first vital enzyme of the glycolytic pathway, which can promote the uptake of glucose into glioma cells via GLUTs by glucose phosphorylation reaction [ 103 ]. Numerous studies reported the upregulation of hexokinase isoform 2 (HK2) in cancer cells and its association with the overall survival of patients with glioma [ 104 , 105 , 106 ]. Zheng et al investigated the mechanism of lncRNA MACC1-AS1-mediated progression of glioma.…”
Section: Lncrnas Modulate Aerobic Glycolysis Of Gliomamentioning
confidence: 99%